ANALISIS POLA ASUH ORANG TUA KORBAN PENYALAHGUNAAN NARKOBA DI RECOVERY CENTER YAYASAN CARITAS PSE - Sryenda Marcelina Kembaren (Welfare StatE, 2013)
Parents have different ways in educating and caring for their children where sometimes parents do not realize their mistakes or shortcomings are to drudge for a living and fulfill every desire of the child would be enough material and ultimately prefer drugs as a last . By looking at the rapid amount of drug abuse, the Government made ​​a policy with Supreme Court Circular No.7 of 2009 on the Placement of Drug Users to Panti therapy and rehabilitation, and Act 35 of 2009 RI Narcotics Article 54 and Article 55 paragraph 1 and 2. This study aims to determine how parenting parents Drug abuse victims in Recovery Center Yayasan Caritas PSE to analyze the status of the position of the child and parents attitudes factor that would eventually form a pattern of care. This is a descriptive study that aims to identify and describe how to apply parenting parents of victims of drug abuse by using descriptive analysis with a qualitative approach. The unit of analysis in this study is 3 rehabilitation patients at Recovery Center Yayasan Caritas PSE. The data collection technique is the study of literature, observation and in-depth interviews. The results of data analysis showed that the pattern established parenting is permissive parenting with an equation that three elderly victims of drug abuse lacks firmness in making decisions related to the victim abuse and tend to rely on any activities undertaken by them. Keyword : Parenting, Victims Of Drug Abuse